Don’t look a gift horse in the mouth? Some reflections around the effects of international cooperation as an instrument to promote economic development - Venero Espinoza, Willy Hernando (2017)
The effects of foreign aid in the process of economic growth in developing countries is a subject of intense debate. While its favorable effects in the struggle with poverty are undeniable, its determining factor for economic development has positions in favor and against. This article presents a review of the literature on foreign aid, focusing on the fundamental aspects to facilitate its analysis. Other aspects that are addressed are the main arguments used to support the granting and receiving of foreign aid towards a developing country, as well as those arguments that criticize its suitability. The final part includes some conclusions about the presented arguments.